2021
DOI: 10.1108/gkmc-08-2020-0109
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of research output in open access journals in BRICS countries: a bibliometric study

Abstract: Purpose This paper aims to investigate the current status of research output published in open access (OA) journals from Brazil, Russia, India, China and South Africa (BRICS) countries from 2010 to 2019 and compare their performances in terms of OA research output. Design/methodology/approach Papers contributed by the researchers of BRICS countries were searched using an advanced search option in the Web of Science core collection database. The retrieved results were restricted to the “journal articles” publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The remarkable growth occurred after 2012, during which time 71.8% of the total outputs were published. This dramatic increase followed the global trend of increasing academic publications in recent years (Mu et al, 2016;Zia, 2021). At the same time, it coincided with the remarkable growth of scientific research in China in the past 10 years.…”
Section: Temporal Evolution Of Annual Publicationsmentioning
confidence: 78%
“…The remarkable growth occurred after 2012, during which time 71.8% of the total outputs were published. This dramatic increase followed the global trend of increasing academic publications in recent years (Mu et al, 2016;Zia, 2021). At the same time, it coincided with the remarkable growth of scientific research in China in the past 10 years.…”
Section: Temporal Evolution Of Annual Publicationsmentioning
confidence: 78%
“…Studies have indeed shown that the development and use of open access (OA) vary across countries, as indicated by Lee & Haupt (2021), Moskovkin et al (2021), Pinfield et al (2020), andZia (2021). In the case of Israel, the rate of OA publications has increased from 31.74% in 2010 to 50.41% in 2020, according to SCImago Journal and Country Rank data.…”
Section: Open Access and The Israeli Contextmentioning
confidence: 99%
“…However, the adoption and motivation for OA practices vary among countries and researchers (Iyandemye & Thomas, 2019;Mueller-Langer et al, 2020;Lee & Haupt, 2021;Pinfield et al, 2020;Zia, 2021). According to the European Open Science Cloud (EOSC) Portal, Israel currently lacks an official OA policy at both the national and institutional levels.…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining research output in universities have focused on (1) publications in specific journals or databases and (2) citations or research impact. For instance, Zia (2021) investigated on the status of research output in Open Access (OA) journals from Brazil, Russia, India, China and South Africa between East African Journal of Education and Social Sciences EAJESS September -October 2022, Vol. 3, No.…”
Section: Introductionmentioning
confidence: 99%